Design, Implementation, and Performance Optimization of a ROS Based Autonomous Mobile Robot for Intralogistics in Manufacturing Facilities - Demir, Neslihan; Demircioglu, Pinar; Bogrekci, Ismail (Journal of Automation, Mobile Robotics and Intelligent Systems, 2026)
This article presents the development and optimization of a ROS-based Autonomous Mobile Robot (AMR) designed for intralogistics in manufacturing environments. By integrating robust mechanical design, advanced sensor fusion, and the Hybrid A* path-planning algorithm, the AMR offers significant improvements in flexibility, safety, and efficiency over traditional AGVs. The proposed AMR system enables dynamic, autonomous navigation in complex industrial layouts, responding adaptively to obstacles and varying payloads. Validation in simulated and real-world settings demonstrates the system’s performance in navigation accuracy, energy efficiency, and load-handling capability, highlighting its potential to streamline logistics and reduce operational costs in Industry 4.0 settings.